Early-Onset Seizures in Ischemic Stroke: A Descriptive Cross-Sectional Study - Mohsina Syed; Sumayyah Liaquat; Zainab Saleem; Jay Singh; Rabia Sana; Naila Naeem Shahbaz (Indian Journal of Medical Specialities)
Context: Poststroke seizures are not infrequent neurological sequelae of stroke. Aims: The primary aim of our study is to determine the frequency of early seizures in acute ischemic stroke in our population. Subjects and Methods: It is a descriptive cross-sectional study done at the Department of Neurology, Dr. Ruth K. M. Pfau Civil Hospital Karachi, Pakistan. The duration of the study was of 6 months, from July 2019 to December 2019. All patients who fulfilled the inclusion criteria were enrolled in the study after Institutional Review Board approval. Informed and written consent was obtained from all subjects. A detailed history and clinical examination were carried out and all patients were assessed by a trained neurologist. Results: Total 281 patients with ischemic stroke were included. One hundred and eighty-one patients (64.4%) were male and 100 (35.6%) were female with a mean age of 48.41 ± 8.730 years. The early-onset seizures were noted in 22 patients (7.8%). In our study, early-onset poststroke seizures were noted more commonly in the age group of 36–60 years and were predominant in the males. Patients with infarction in the parietal lobe exhibited greater seizure occurrence. The most common seizure type observed was generalized tonic–clonic. Majority of early-onset poststroke seizures occurred in the 1st week. Conclusion: In our study, the frequency of early onset seizures in patients with ischemic stroke was found to be 7.8%, which when occurs increases morbidity.